2008
DOI: 10.1124/dmd.108.021089
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of a Hepatic Transporter Multidrug Resistance-Associated Protein 2 Is Involved in Alteration of Pharmacokinetics of Glycyrrhizin and Its Metabolites in a Rat Model of Chronic Liver Injury

Abstract: ABSTRACT:Glycyrrhizin (GL) has been used to treat chronic hepatitis in Japan and Europe. It is thought to induce pseudoaldosteronism via inhibition of type 2 11␤-hydroxysteroid dehydrogenase (11␤-HSD2) by glycyrrhetinic acid (GA), a major metabolite of GL. A previous clinical study suggested that 3-monoglucuronyl-glycyrrhetinic acid (3MGA), another metabolite of GL, might play a more important role in the pathogenesis of pseudoaldosteronism. The present study evaluates the pharmacokinetics of GL and its metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 29 publications
(31 reference statements)
1
36
0
Order By: Relevance
“…Further investigation is needed to verify this hypothesis. Although evidence suggests that Oatp or Mrp2 alone may contribute to liver accumulation or biliary excretion of saponins such as dioscin and glycyrrhizin (Makino et al, 2008;Zhang et al, 2013), this is the first report of cooperation by uptake transporters (Oatp) and efflux transporters (Bcrp/Mrp2) in the hepatobiliary disposition of saponins. Although 70% of the absorbed TB-2 was excreted into the bile and a significant double-peak phenomenon was observed, the bioavailability of TB-2 was only 1.1% after oral administration of 180 mg/kg (Cai et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigation is needed to verify this hypothesis. Although evidence suggests that Oatp or Mrp2 alone may contribute to liver accumulation or biliary excretion of saponins such as dioscin and glycyrrhizin (Makino et al, 2008;Zhang et al, 2013), this is the first report of cooperation by uptake transporters (Oatp) and efflux transporters (Bcrp/Mrp2) in the hepatobiliary disposition of saponins. Although 70% of the absorbed TB-2 was excreted into the bile and a significant double-peak phenomenon was observed, the bioavailability of TB-2 was only 1.1% after oral administration of 180 mg/kg (Cai et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For example, dioscin, a steroid saponin with very low bioavailability (0.2%), is a substrate of organic anion-transporting polypeptides (Oatp), which are responsible for the extraction of substrates from blood into the liver; thus, the concentration of dioscin in the liver is high after intravenous injection (Zhang et al, 2013). Glycyrrhizin, a triterpene saponin with low bioavailability (4%), is a substrate of multidrug resistance-associated protein 2 (Mrp2), which mediates biliary excretion (Makino et al, 2008), consistent with 98% of unmodified glycyrrhizin being excreted into the bile after intravenous administration (Yamamura et al, 1991). However, to the best of our knowledge, there is no published study to clarify the contribution of hepatic transporters to the hepatobiliary disposition of TB-2, and the metabolic capacity of TB-2 in the liver has not been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…1) (Makino et al, 2008). In contrast, urinary excretion of GA was very low regardless of its high plasma concentration when GL was administered orally to rats (Makino et al, 2008).…”
Section: Introductionmentioning
confidence: 89%
“…13) Because the plasma and urinary levels of 3MGA in liver fibrosis model rats were higher than those in controls, we examined the mechanism of the renal excretions of GA and 3MGA. At first, using bovine serum albumin and normal rat serum, the authors examined the albumin-binding rates of 3MGA and GA using an ultrafiltration method and found that both 3MGA and GA were present as forms bound to albumin in ratios exceeding 99.9%.…”
Section: )mentioning
confidence: 99%
“…Using this model, the authors examined the pharmacokinetics of the licorice component and its metabolite. [13][14][15] The authors orally administered GL to the hepatic fibrosis model rats or control rats, and compared the profiles of the plasma concentrations of each metabolite between these rats. Higher levels of GL and 3MGA were found in the plasma of hepatic fibrosis model rats than in control rats.…”
Section: )mentioning
confidence: 99%